Approche régulationniste de la diversité des dispositifs institutionnels environnementaux des pays de l’OCDE - Luc Elie; Bertrand Zuindeau; Mathieu Bécue; Mamoudou Camara; Ali Douai; André Meunié (Revue de la Régulation)
This paper analyses the hypothesis of a diversity of “environmental institutional devices” (EID) within OECD countries from a traditional regulationist point of view on the diversity of capitalisms. Using multidimensional statistical analysis, we highlight the factorial axes that structure this diversity and we build an EID based typology of countries. A comparison follows with the typology of capitalisms of Amable (2005). This comparison appears to be only conclusive for liberal and Mediterranean models of capitalism. One explanation of this link seems to be found using an analysis of the institutional complementarity between EID and the institutional areas that build Amable’s models of capitalism.